Effects of pre-irradiation and SDF-1 suppression on the progression of murine astrocytoma cells grown in different stromal beds. (December 2014) - Yu, Ching-Fang; Lin, Chi-Min; Wang, Shu-Chi; Chen, Fang-Hsin; Hong, Ji-Hong; Tsai, Chien-Sheng; Yang, Ying-Chieh; Chiang, Chi-Shiun
Abstract Purpose: To examine whether brain tumors grown in pre-irradiated (PreIR) thigh have a similar tumor bed effect (TBE) as in PreIR brain tissue. Material and methods: Tumor growth delay and immunohistochemical (IHC) staining for CD31, an endothelial surface marker, and PIMO, a hypoxia marker, were used to study the TBE of a murine astrocytoma, ALTS1C1, or a stromal-derived factor-1 (SDF-1) gene-silenced astrocytoma, ALTS1C1-SDFkd, growing in different PreIR stroma beds. Results: ALTS1C1 tumors growing in both PreIR brain and PreIR thigh had reduced microvascular density (MVD) and more chronic hypoxia, but tumor growth delay was only seen in PreIR brain tissue. In contrast, ALTS1C1-SDFkd tumors showed tumor growth delay in PreIR thigh, with little effect in PreIR brain tissue. Conclusions: This study cautions that both the tumor and the nature of the PreIR stromal bed are important when using pre-irradiation as a model of recurrent brain tumors after radiation therapy.